2019
DOI: 10.1016/j.cbpa.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory flow in the sturgeon is externally driven

Abstract: Fluid dynamics plays an important part in olfaction. Using the complementary techniques of dye visualisation and computational fluid dynamics (CFD), we investigated the hydrodynamics of the nasal region of the sturgeon Huso dauricus. H. dauricus offers several experimental advantages, including a well-developed, well-supported, radial array (rosette) of visible-by-eye olfactory sensory channels. We represented these features in an anatomically accurate rigid model derived from an X-ray scan of the head of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Fig. 5C of Garwood et al, 2019) was found over 12 s to vary by < 0.02 %. Velocities, static pressures, and shear stresses were the averages of the last 500 iterations from a total of 2000 iterations of a converged, time-averaged solution to the Navier-Stokes equations.…”
Section: Generalmentioning
confidence: 89%
See 4 more Smart Citations
“…Fig. 5C of Garwood et al, 2019) was found over 12 s to vary by < 0.02 %. Velocities, static pressures, and shear stresses were the averages of the last 500 iterations from a total of 2000 iterations of a converged, time-averaged solution to the Navier-Stokes equations.…”
Section: Generalmentioning
confidence: 89%
“…Most of the methodology used here has been described before (Cox, 2008;Abel et al, 2010;Holmes et al, 2011;Howard et al, 2013;Ramsey et al, 2015;Garwood et al, 2019). We therefore give only brief descriptions here.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations